Rheology on CNT-filled polymer nanocomposites (II) - Chan, Xue Shuang. (2012)
In this study, multi-wall carbon nanotubes (MWCNTs) were chemically functionalized through acid treatment. The MWCNTs filled polypropylene (PP) composites were prepared by employing acid-treated MWCNTs through melt compounding using a twin-screw extruder. Polypropylene grafted maleic anhydride (PP-g-MA) was added to the nanocomposites as a compatibilizer to promote the dispersion of carbon nanotubes. Images produced by the Field Emission Scanning Electron Microscopy (FE-SEM) have shown that the distribution of the acid treated MWCNTs was more uniform than pristine MWCNTs. The effect of employing acid-treated MWCNTs allowed for better dispersion and interfacial interaction between the acid-treated MWCNTs and PP matrix. A major focus was to investigate on the influence of acid-treated MWCNTs and pristine MWCNTs on the rheological properties of the composite system for different MWCNTs concentration. When acid-treated MWCNTs were added, the increase in dynamic moduli and viscosity were more significant as compared to the composite system containing pristine MWCNTs. With the addition of acid-treated MWCNTs, the rheological percolation threshold drops from 2 wt% to 1.5 wt%. The gel point (Cg) value for pristine MWCNTs/PP-g-MA/PP and acid treated MWCNTs/PP-g-MA/PP was 2.0 wt% and 1.5 wt% respectively.